Fundamental properties of copper-doped and co-doped sno2of lithium potassium borate glass exposed to photon below 4gy - Namma, Haydar Aboud (2013)
The glass samples of composition 10K2CO3 ? (90 ? x) H3BO3 with 10 = x = 30, 20Li2CO3 ? 10K2CO3 ? (70 ? x) H3BO3 ? xCu with 0.05 = x = 1.0 and 20Li2CO3 ? 10K2CO3 ? (69.9 ? x) H3BO3 ? 0.1Cu ? xSnO2 with 0.05 = x = 0.2 have successfully been prepared by melt-quenching technique. The samples were analyzed by X ? ray diffraction spectrometer to confirm that the sample is amorphous. The energy band gap measurements of the glass samples reveal that, introducing copper into lithium borate glass reduce the energy band gap of the samples, while the addition of SnO2 into Cu-doped sample increase the energy band gap. The impact of SnO2 gives an enhancement in the luminescence intensity by almost 3 times when 0.1 mol% SnO2 was added to 0.1 mol% Cu-doped borate glass. The peaks shapes shifted from blue luminescence to blue and green luminescence for Cu-doped and co-doped samples respectively. The thermoluminescence (TL) properties of Cudoped and co-doped with SnO2 glass were investigated in this work. The glow curves position of Cu-doped and co-doped with SnO2 glass were recorded at 205?C and 215?C respectively at a heating rate of 20?Cs?1. In addition, the optimum annealing procedure of Cu-doped and co-doped with SnO2 glass was 20 min at 400 ?C and 30 min at 400?C respectively. The highest TL intensity of Cu-doped sample was recorded at Cu concentration of 0.1 mol%. The highest TL intensity for co-doped with SnO2 glass was observed at SnO2 concentration of 0.1 mol%. The linear relationship of dose?TL intensity was observed for both glass samples for different doses ranging from 0.5 to 4.0 Gy subjected to 6, 10 and 12 MV X-ray photon energies and Co?60 gamma ray. The co-doped with SnO2 glass has always higher TL response compared to Cu-doped glass. The study of fading characteristics shows that co-doped with SnO2 glass has lower fading compared to Cu-doped glass. Reproducibility study of both types of glasses show the thermoluminescence intensity of Cu-doped glass are slowly decreasing about 1.6% with the repeating readout and about 1.3% for co-doped with SnO2. Study on the TLD sensitivity shows that the co-doped with SnO2 glass is almost 6 times more sensitive than the Cudoped glass. The TL sensitivity was found as 75 ?C g?1Gy?1 and 266 ?Cg?1Gy?1 for Cu-doped and co-doped with SnO2 glass respectively. The relative energy response of Cu-doped and co-doped with SnO2 glass have been calculated theoretically for photon energies up to 1.25 MeV and it is found that the theoretical calculations are in good agreement with the experimental results. The average value of activation energy and the average frequency of Cu-doped and co-doped with SnO2 glass are calculated.